Effects of magnesium intake deficiency on bone metabolism and bone tissue around osseointegrated implants - Belluci, Marina Montosa [UNESP]; Giro, Gabriela [UNESP]; Landazuri del Barrio, Ricardo Andres [UNESP]; Rodrigues Pereira, Rosa Maria; Marcantonio, Elcio [UNESP]; Orrico, Silvana Regina Perez [UNESP] (Wiley-Blackwell, 2011)
Objectives: This study evaluated the effect of magnesium dietary deficiency on bone metabolism and bone tissue around implants with established osseointegration.Materials and methods: For this, 30 rats received an implant in the right tibial metaphysis. After 60 days for healing of the implants, the animals were divided into groups according to the diet received Control group (CTL) received a standard diet with adequate magnesium content, while test group (Mg) received the same diet except for a 90% reduction of magnesium. The animals were sacrificed after 90 days for evaluation of calcium, magnesium, osteocalcin and parathyroid hormone (PTH) serum levels and the deoxypyridinoline (DPD) level in the urine. The effect of magnesium deficiency on skeletal bone tissue was evaluated by densitometry of the lumbar vertebrae, while the effect of bone tissue around titanium implants was evaluated by radiographic measurement of cortical bone thickness and bone density. The effect on biomechanical characteristics was verified by implant removal torque testing.Results: Magnesium dietary deficiency resulted in a decrease of the magnesium serum level and an increase of PTH and DPD levels (P <= 0.05). The Mg group also presented a loss of systemic bone mass decreased cortical bone thickness and lower values of removal torque of the implants (P <= 0.01).Conclusions: The present study concluded that magnesium-deficient diet had a negative influence on bone metabolism as well as on the bone tissue around the implants.
Keywords: bone markers; dental implants; magnesium deficiency; rat